Peran Seni Kriya Dalam Mendukung Pariwisata Berbasis Budaya di Desa Penglipuran, Bali - Mukti, Masetya; Dijani, Karenina Mauren (Hastagina : Jurnal Kriya Seni, 2025)
Penglipuran Village in Bangli Regency, Bali is one example of a culture-based tourism village that successfully prioritizes the preservation of traditions, the natural environment, and the empowerment of local communities. The village maintains the traditional Balinese spatial and architectural layout that has been passed down from generation to generation, reflecting the values of life philosophy, harmony, and sustainability. In addition, Penglipuran Village also develops the potential of craft art, especially bamboo plaiting and various other traditional crafts, as a leading tourist attraction. These craft products are not only an economic commodity, but also serve as a medium for preserving authentic local cultural values. Crafts in this village become a means of cultural expression that strengthens community identity and enriches the tourist experience through direct interaction with the creative process and traditional values. Tourism management in Penglipuran Village is conducted collaboratively between the indigenous community, local government, and local businesses. This management model encourages active community participation in maintaining a balance between cultural preservation and economic development. This research uses a descriptive qualitative approach with observation, interview, and documentation methods to explore the role of craft in supporting the development of tourism villages. The results showed that the existence of craft art not only strengthens the image of Penglipuran Village as a unique and authentic cultural destination, but is also able to improve community welfare through job creation, income generation, and sustainable preservation of cultural heritage. Thus, Penglipuran Village becomes a real representation of the harmonious integration between culture, economy, and environment within the framework of community-based tourism development